PENGARUH KOMPOSISI BAHAN TERHADAP KARAKTERISASI BRIKET LIMBAH BIJI JARAK PAGAR (JATROPHA CURCAS LINN) - Sriharti, -; Salim, Takiyah (LIPI Press, 2011)
An experiment on the infl uence of material composition to the characteristic of the briquette jatropha seed waste (Jatropha curcas Linn) has been done. The material consist of jatropha seed waste, rice husk, jatropha seed shell waste and coconut shell. The methods of briquette processing were conducted with carbonization and pressing with hydraulic manual system with capacity of 16 briquette per batch. The result of chemical characteristics of jatropha briquette shows that moisture content, calorie value, fulfi ls the Indonesian National Standards (SNI) number 01-6235-2000, whereas ash content does not fulfi ls the SNI. The result of experiment showed that physical characteristics of jatropha briquette including initial and relaxation density fulfi ls the SNI. The composition of material jatropha seed waste with coconut shell showed the best result with combustion rate of 18.61 gram/minute, specifi c consumtion of fuel 0.0997 gram fuel/gram water, combustion power 161.961 watt and thermal effi ciency 74.27 %.